3' cycle-labeled oligonucleotides with predictable length for primer extension and transgene analysis. - Tsai, C J (1996)
Efficient labeling of short oligos at their 3'-ends was achieved through polymerase chain reaction. The length of cycled-labeled oligos can be accurately predicted by omitting one or more dNTPs in the labeling step. Thus, labeled oligos can be simply column-purified, eliminating the need for tedious gel purification. We demonstrated the effectiveness of this technique in determining the transcription start site of a given gene and in transgene analysis to differentiate the transcript of an endogenous gene from that of an introduced homologous gene. This technique could be widely extended to other molecular biology applications in which labeled oligos are employed.